1985
DOI: 10.1002/1097-0142(19850715)56:2<249::aid-cncr2820560207>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Early resection of residual tumor during cisplatin, vinblastine, bleomycin combination chemotherapy in stage III and bulky stage II nonseminomatous testicular cancer

Abstract: Sixty consecutive patients with Stage III or bulky Stage II nonseminomatous germinal testis tumors were treated with cisplatin, vinblastine, bleomycin combination chemotherapy (PVB). One patient died of acute toxicity after the first course of therapy, 16 entered complete remission (CR) after two or three inductions, and 36 underwent surgery for removal of residual masses after the third cycle. No residual tumor was found in 16 cases, 10 had mature teratoma, and residual malignant tumor was completely resected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
2

Year Published

1985
1985
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 15 publications
1
15
0
2
Order By: Relevance
“…hematologic and gastrointestinal toxicity was much less severe in the PEB series than in a precedent group of patients treated with PVB. 9 Better experience with drugs and disease, appropriate use of surgery, and salvage chemotherapy have improved the overall cure rates of disseminated testicular cancer from 57% to 81% in three consecutive PVB series. '-' But if we look at the cure rates achieved with PVB and surgery alone, we realize that they have reached a plateau at 60% to 70% and that the cure rates of patients with more advanced disease are in the range of 40% to 50%.…”
Section: Discussionmentioning
confidence: 99%
“…hematologic and gastrointestinal toxicity was much less severe in the PEB series than in a precedent group of patients treated with PVB. 9 Better experience with drugs and disease, appropriate use of surgery, and salvage chemotherapy have improved the overall cure rates of disseminated testicular cancer from 57% to 81% in three consecutive PVB series. '-' But if we look at the cure rates achieved with PVB and surgery alone, we realize that they have reached a plateau at 60% to 70% and that the cure rates of patients with more advanced disease are in the range of 40% to 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, complete bilateral resection was considered necessary 13,14 . However, others have proposed excising the only the residual tumor 15–17 . In the present study, the residual masses were not large and patients hoped for normal ejaculation.…”
Section: Discussionmentioning
confidence: 53%
“…There has been controversy about the resection area for RPLND after chemotherapy. Some authors reported that complete bilateral resection should be necessary, others proposed excising only the residual tumor . Heidenreich et al .…”
Section: Discussionmentioning
confidence: 99%